PENGARUH MODAL, JAM KERJA DAN TINGKAT PENDIDIKAN TERHADAP PENDAPATAN PEDAGANG SEKITAR KAMPUS UIN ALAUDDIN MAKASSAR - sulaiman, sitti aisyah (ICOR: Journal of Regional Economics, 2021)
Abstract The purpose of this study is to determine the effect of capital, working hours and level of education on merchants' income around the campus of UIN Alauddin Makassar. This study uses the variable X, namely capital, working hours and education level, while the variable Y is income. The type of research used is quantitative. The Data Collection Technique In This Research, That Is By Observation And Questionnaires. The sample in this study amounted to 60 people. Data Analysis Method Is Multiple Regression. The results of this study are, 1). There is a significant influence between capital and merchants' income, with a significant value = 0.000. 2). There is a significant effect between working hours on traders' income, with a significant value = 0.038. 3). There is no significant influence between the level of education on the merchant's income, with a value of 0.333. Keywords: Traders, Capital, Working Hours, Education